0183 Improving our in-situ video recording and feedback system via manufacturer collaboration. (2nd November 2015) - Gay, Christopher; Riby, Stuart; Graby, Matthew; Charlton, Olivia
Abstract : Background/context: HILS perform numerous In-situ simulations, aspiring to replicate the 'in centre' quality in the clinical environment, including video feedback. Over time we have increased the quantity and quality of our in-Situ simulations, most recently assimilating our current video feedback system in collaboration with Scotia to create a personalised 'SMOTS in a box'. Description of innovation or topic: Time, space, usability and durability are all key concerns for in-situ simulation in a clinical environment. There are increasing pressures on the technical team for fast and efficient setups and take downs – HILS previously used SMOTS Pack&Go, which does address some of these issues; it was safer transporting a camera system from site to site, and more adaptable to the environment. However it wasn't simple or quick to assemble and it lacked durability. We highlighted our requirements and collaborated with Scotia to create a solution that met our needs. Improvements/outcomes (anticipated or recorded): Set up and take down of the equipment is simpler and quicker, with minimal induction training needed by technicians. The durability of this tool has meant little or no technical complications meaning no disruption or delay to teaching sessions due to troubleshooting. Transport of this expensive resource is also much easier and safer. Space used by this tool has been reduced, which makes it easier for the clinicians to train in the environment. Take home messages: As the demand increases for In-Situ education, so will the demand for improved products like this. We have successfully helped improve a key piece of hardware used regularly for high fidelity in situ simulation. This was a successful collaboration to create a solution that benefits many.